Polymorphism of Cyt-b Gene in Several Indonesian Cattle Using PCR-RFLP Method - Agung, Paskah Partogi; Perwitasari, Dyah; Farajallah, Achmad; Said, Syahruddin; Kaiin, Ekayanti Mulyawati; Saputra, Ferdy; Hermansyah, Alfandy; Kuswati, Kuswati; Susilorini, Tri Eko; Zein, Moch. Syamsul Arifin (Faculty of Animal Science, Universitas Gadjah Mada, 2024)
The cytochrome b (Cyt-b) gene is one of the genes that is located in the mitochondrial DNA. Variations in the Cyt-b gene can be used to compare different animal species to investigate the origin of certain animal species. This study aimed to assess the genetic diversity of Indonesian local cattle breeds, including Bali cattle as an Indonesian native cattle breed and Banteng as the wild type of Bali cattle, using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). A total of 336 individual DNA samples from Indonesian cattle breeds were analyzed in this study. The RFLP method using three restriction enzymes, i.e., HinfI, HaeIII, or XbaI, was used to identify the variation of the Cyt-b gene. The Cyt-b gene was polymorphic based on the PCR-RFLP method. There were six alleles of the Cyt-b gene found in this study, i.e., A and B allele (HinfI), C and D allele (HaeIII), X and Y allele (XbaI). All alleles can be found in Pasundan, Madura, and PO cattle. Pesisir cattle have the highest allele frequency D. The UPGMA results showed three clusters of Indonesian native cattle in this study. Cluster 1 consists of Pasundan, Banteng, and Bali cattle. Cluster 2 consists of Madura, PO, and SO cattle. Pesisir was separated from other cattle in cluster 3. The X allele could become an indicator to distinguish Banteng and Bali cattle.